Peran Mediasi Komitmen Afektif pada Pengaruh Etika Kerja Islami Terhadap Kinerja Pegawai - Ibnu Ibnu; Marwan Man Soleman (Jurnal Ekonomi Manajemen Akuntansi, 2025)
This study analyzes the influence of Islamic work ethics on employee performance, with affective commitment as a mediating variable. Using a descriptive quantitative approach, the study involved 165 employees from a total population of 279, selected through purposive sampling. Data were analyzed using the PLS-SEM method. The results indicate that Islamic work ethics have a positive and significant effect on both employee performance and affective commitment. Additionally, affective commitment has a positive and significant impact on employee performance. Affective commitment mediates the influence of Islamic work ethics on employee performance, suggesting that the implementation of Islamic work ethics can enhance both affective commitment and employee performance within an organization.